Light green background enhances reading performance in visual display terminal tasks - Xiangyun Li; Xiangyun Li; Yu Guan; Yu Guan; Ruilin Wu; Xuejun Bai; Xuejun Bai; Xuejun Bai (Frontiers in Psychology, 2025)
Visual context plays an important role in reading behavior. However, the effects of background color on reading performance remain underexplored. This study investigated how background color (white vs. light green) affects reading performance, visual fatigue, emotion, and physiological responses in first language (L1, Chinese) and second language (L2, English) reading contexts. Forty university students completed reading tasks under both background color conditions, and self-report, behavioral, eye-tracking, and physiological data were collected. The results showed differential effects of background color across L1 and L2 reading contexts. In L1 reading experiment, a light green background significantly increased pupil diameter (indicating lower visual fatigue), reduced negative emotion, and improved reading performance compared to a white background. Moreover, background color significantly affected skin temperature among female participants only. In L2 reading, the green background also increased pupil diameter, though this effect was limited to female readers, with no significant improvements in reading performance or emotional response. These findings suggest that perceptual features of digital reading environments can influence multiple aspects of reading, including visual fatigue, emotion, and performance, with varying effects across L1 and L2 reading contexts. Notably, the effects of background color appear to be moderated by task complexity and gender, with female readers showing greater sensitivity to background color effects, particularly under more demanding reading conditions. The study highlights the role of individual differences and perceptual context in shaping reading experience, with implications for interface design and digital learning platforms.